The Impact of Intensive Fish Farming on Pond Sediment Microbiome and Antibiotic Resistance Gene Composition - Lastauskienė, Eglė; Valskys, Vaidotas; Stankevičiūtė, Jonita; Kalcienė, Virginija; Gėgžna, Vilmantas; Kavoliūnas, Justinas; Ružauskas, Modestas; Armalytė, Julija (Frontiers in Veterinary Science, 2021)
Aquaculture is a fast-growing animal food sector, and freshwater fish farming is particularly common in Central and Eastern Europe. As the biodiversity of fishery ponds is changed toward fulfilling the industrial needs, precautions should be taken to keep the system sustainable and protect the adjacent environment from possible damage. Due to risk of infectious diseases, antibiotics are used in aquaculture production systems. The constant exposure to antimicrobials can contribute to the rise of antibiotic resistance in aquaculture products and the adjacent ecosystems, with possibility of dissemination to the wider environment as well as between animals and humans. Even though previous studies have found antibiotic resistance genes in the sediments and water of farming ponds, the tendency and direction of spreading is not clear yet. The objective of this project was to evaluate the influence of intensive fish farming on the condition of water bodies used for the aquaculture and the environment, concentrating on the impact of the aquaculture on the surrounding water ecosystems as well as the possibility of transferring the pollutants and antibiotic resistance genes to both environment and the human hosts. Combined measurement of antibiotic and heavy metal contamination, toxicity assessment, microorganism diversity, and the detection of common antibiotic resistance genes was performed in the sediments of one fishery farm ponds as well as sampling points upstream and downstream. All the tested sediment samples did not show significantly elevated heavy metal concentrations and no substantial veterinary antibiotic pollution. From the antibiotic resistance genes tested, the presence of aminoglycoside and β-lactam resistance determinants as well as the presence of integrons could be of concern for the possibility of transfer to humans. However, despite the lack of heavy metal and antibiotic pollution, the sediments showed toxicity, the cause of which should be explored more.